Requirements for Establishing Energy Hubs: Practical Perspective - Mahmoud A. Hammad; Sara Elgazzar; Borut Jereb; Marjan Sternad (Amfiteatru Economic, 2023)
The global economy has barely begun to recover from the effects of the COVID-19 pandemic, only to be thrown into a new crisis because of the Russian-Ukrainian war. The war exacerbated the energy problem by causing a shortage of energy supplies for the EU and other countries, affecting quality of life. As a result, establishing energy hubs for collecting, processing, storing, and transiting energy resources between producing and consuming countries has become imperative to manage energy supplies efficiently. However, previous studies have not yet addressed the requirements for setting up energy hubs from a practical point of view. Therefore, this paper investigates the requirements for the establishment of energy hubs, particularly for oil and gas, from a practical perspective. The researchers conducted 13 semi-structured interviews with different energy stakeholders. Using the SWOT analysis matrix tool, the findings assessed the current state of the global oil and gas market, and the main practical requirements for the establishment of energy hubs were identified, along with the elements for implementation. Furthermore, the article highlighted the most pressing practical issues confronting the establishment of energy centres. Finally, the paper laid out a comprehensive practical framework based on the industry practitioners views to help establish energy hubs. The framework provides a possible guide for countries to establish energy hubs based on the main requirements outlined in this study. It can also improve the diversity, flexibility, and security of energy supply, especially for countries that rely on sole suppliers, such as the EU.
Keywords: O13; P18; P48; Q42; 330; Energy hubs; energy stakeholders; diversification of energy supplies; security and sustainability of energy supply; European Union countries; Russian-Ukrainian war.